A Negative Theory of Justice: Towards a Critical Theory of Power Relations. Issue 164 (1st September 2020) - Mazzone, Leonard
Abstract: This article outlines the chief challenges concerning the philosophical theories of emancipation and clarifies the solutions provided by a so-called negative theory of justice. Besides highlighting the classic questions that every philosophical theory of emancipation is expected to answer, the article aims to highlight the link between this theoretical framework and an immanent critique of conditions of domination. Moreover, it sheds light on the main differences between this theoretical perspective and Honneth's theory of recognition, Fraser's three-dimensional conception of justice, and the critique of power relations recently advanced by Rainer Forst. The comparative analysis of these theoretical approaches will make it possible to highlight and appreciate the main merits of a so-called negative theory of justice that combines a multidimensional diagnosis of existing asymmetries of power with an immanent critique of their justifications.